A study on perception towards statistics field among Diploma Statistics students / Muhammad Emir Fakhry Abdul Manan, Nur Izzatul Azyyati Suhaimi and Safwani Lahak - Abdul Manan, Muhammad Emir Fakhry; Suhaimi, Nur Izzatul Azyyati; Lahak, Safwani (2020)
Statistics represent scientific ways or methods for collecting, organising, analysing, interpreting and presenting data as useful information to draw valid conclusions and make effective decisions. All kinds of scientific needs to be proficient in using statistics so people would be able to use what data show efficiently. Advanced level coursework will require people to demonstrate the ability to use data effectively by using statistics. People will need to calculate and draw graph or charts to identify the important features of the data and provide insights into the type of models and analysis that should be used. The ability to use descriptive statistics is important to presenting the data in meaningful form. Inferential statistics in also important to make inferences from samples to populations. By using statistics, people won't need to use every single possible result to form a valid conclusion. If people use statistics well, the data can be collected in minimum amount to support or reject a hypothesis. It will also help to reduce amount of work that should be done.